(untitled) (Passagens: Revista Internacional de História Política e Cultura Jurídica, 2025)
Smart contracts, a revolutionary technology that offers a digital alternative to conventional contracts, are popular. Smart contracts also known as automated digital contracts are becoming common in various countries due to their efficiency and openness. Various national and global forums have agreed that smart contracts might alter contract enforcement and boost economic development in India. Given this, it’s crucial to understand the Indian Contract Act, (ICA) 1872 stance on smart contracts. ICA requires testing smart contracts for contractual validity before entering the uncharted seas of autonomous and anonymous digital contracting. This experiment raises many issues, especially given the law’s strict procedural structure. This article refutes the claim that smart contracts should be regulated by self-regulation. Rather author prefers a broad interpretation of substantive contractual law to harmonize smart contracts under the ICA, following common law’s flexibility. It is shown that smart contracts are built on the same principles as common law contracts and deepen our research in the framework of Indian law and precedent. Similar approaches from other countries support this perspective. Although many legislations require change, it is believed that a smart contract law is not needed. The paper concludes by proposing solutions to the potential obstacles that may arise due to present approach.